Venezuelan women according to Radio Rumbos, 70's of the 20th century (Mayéutica Revista Científica de Humanidades y Artes, 2018)
Radio has become the modern format of orality. And from the oral tales told from parents to children, from minstrels, from theater actors, we pass to the most formidable stories narrated from a booth, behind a microphone and with incidental music. From those oral experiences, in which it was necessary to see the face of the speaker, we began to imagine the face of the voice and symbolize the sound carried by the hertzian waves. Thus, the detailed description of a character, a landscape, an action, a fact reaches our subconscious, inculcates new thought patterns, and when we least realize, we are putting into practice new actions, which reinforce habitus and cultures. We present a historical essay whose purpose is to approach the construction of the role of women based on Radio Rumbos programming in the decade of the 70s of the last century. Programs like Martín Valiente, El Derecho de Nacer, or La Vida de Las Canciones disseminated gender discourses that could cement the image of the Venezuelan woman as a housewife, as a sexual object and face the moral standards of the society of those years to then erect the Venezuelan woman with a new way of thinking about moralistic concepts such as virginity, marriage and sex. Radio Rumbos presented the Venezuelan society with the ideal models of women and with these they proposed their concept of femininity in that decade.
Keywords: culture; Radio Rumbos; femininity; gender